Synthesis and anti-viral activity of novel tripeptidyl compounds, modification of graphene oxides, and synthesis of peptidyl substrates for use in an electrochemical biosensor device - Prior, Allan Mark (Kansas State University, 2013)
Three research projects are described in this dissertation and they consist of the discovery of norovirus protease inhibitors, modification of graphene oxides (GO) for the detection of norovirus, and design and fabrication of nanoelectronic device based on nanocarbon fibers for the detection of breast cancer proteases, legumain and cathepsin B. A novel class of tripeptidyl anti-noroviral compounds which strongly inhibit NV3CL[superscript]pro in enzyme and cell based assays was discovered. An example of one of the most active compounds is (1-{3-methyl-1-[2-oxo-1-(2-oxo-pyrrolidin-3-ylmethyl)-ethylcarbamoyl]-butylcarbamoyl}-2-naphthalen-1-yl-ethyl)-carbamic acid benzyl ester, which showed an IC₅₀ value of 0.14 ± 0.2 μM (enzyme assay) and EC₅₀ value of 0.04 ± 0.02 μM (cell based assay). This compound has an aldehyde warhead, a P1 glutamine surrogate, a P2 leucine, a P3 L-1-napthylalanine and an N-terminal carboxybenzyl cap. The corresponding bisulfite adduct, 2-[2-(2-benzyloxycarbonylamino-3-naphthalen-1-yl-propionylamino)-4-methyl-pentanoylamino]-1-hydroxy-3-(2-oxo-pyrrolidin-3-yl)-propane-1-sulfonic acid monosodium salt, has a comparable activity in enzyme and cell based assays (IC₅₀ 0.24 ± 0.1 μM; EC₅₀ 0.04 ± 0.03 μM). (1-{3-methyl-1-[2-oxo-1-(2-oxo-pyrrolidin-3-ylmethyl)-ethylcarbamoyl]-butylcarbamoyl}-2-naphthalen-1-yl-ethyl)-carbamic acid benzyl ester and its ketoamide derivative, (1-{1-[2-isopropylcarbamoyl-2-oxo-1-(2-oxo-pyrrolidin-3-ylmethyl)-ethylcarbamoyl]-3-methyl-butylcarbamoyl}-2-naphthalen-1-yl-ethyl)-carbamic acid benzyl ester, exhibited very good broad spectrum anti-viral activity, especially in human rhino virus and severe acute respiratory syndrome bioassays. We demonstrated that the surface of graphene oxide can be chemically modified with t-butylester and carboxylic acid functionalities. Fourier transform infrared spectroscopy, Raman spectroscopy and solid state nuclear magnetic resonance spectroscopy confirmed the presence of t-butylester and carboxylic acid functional groups. One sided oligonucleotide functionalized graphene oxide was synthesized using a solid state technique. A carboxylic acid functionalized graphene oxide was deposited onto the surface of electronic chips to bridge two gold electrodes, using a direct deposition technique. The carboxylic acid functionalized graphene oxide displayed semi-conductive properties and its use in an electronic biosensor device to detect noroviral RNA was investigated. Novel redox-active protease substrate peptides H₂N-(CH₂)₄CO-Ala-Ala-Asn-Leu-NHCH₂-ferrocene and H₂N-(CH₂)₄CO-Leu-Arg-Phe-Gly-NHCH₂-ferrocene were synthesized successfully and used in an alternating current voltammetry technique to facilitate the detection of the cancer related protease enzymes legumain and cathepsin B. After attachment of these peptides to the tips of carbon nanofiber nanoelectrode arrays, the presence of active protease enzymes could be detected as manifest by an exponential decay in current signal detect when monitored by alternating current voltammetry, at initial enzyme concentrations of 80.1 nM (legumain) and 30.7 nM (cathepsin B). The peptide cleavage sites were confirmed by analyses of the cleaved fragments using high performance liquid chromatography and mass spectrometry. Results showed that the cleavage of H₂N-(CH₂)₄CO-Ala-Ala-Asn-Leu-NHCH₂-ferrocene at the C-terminal side of asparagine residues by legumain and cleavage of H₂N-(CH₂)₄CO-Leu-Arg-Phe-Gly-NHCH₂-ferrocene at the C-terminal side of arginine residues by cathepsin B. Legumain exhibited a specificity constant (k[subscript]cat/K[subscript]m) of 11.3 x 10ᶟ M⁻¹S⁻¹ while cathepsin B exhibited a higher value of specificity constant (4.3 x 10⁴ M⁻¹S⁻¹) which agreed with the values obtained from fluorescence enzyme assay.
Keywords: Viral protease inhibitors; 3C protease and 3C-like protease inhibitors; Modification of graphene oxides; Chemistry (0485)